Development of a vortex wind device - Koshumbaev, Marat; Issenov, Sultanbek; Iskakov, Ruslan; Bulatbayeva, Yuliya (Eastern-European Journal of Enterprise Technologies, 2023)
The relevance of the research is related to the development of a new type of renewable energy source ‒ a vortex wind device with a vertical axis of rotation without wind guidance mechanisms. The main purpose of the study is to develop a vortex wind turbine using mathematical modeling of vortex motion and laboratory experiments on the model. The object of the study is a vortex wind device consisting of a concentrator with curved channels, inside which there is a wind wheel, and a vertical pipe mounted on the concentrator. The calculations are based on the method of modeling large vortices with the solution of averaged Navier-Stokes equations. As a result of the research, the velocity distribution in the concentrator, inside the structure and the discharge pipe were obtained. The computational experiment shows that the narrowing channels of the concentrator create a stable vortex motion inside the structure and the vertical pipe. The methods used for calculating turbulent flows allow to study aerodynamic processes in wind turbines with a vortex effect. The absence of a rotary mechanism reduces the risks of breakdowns of rotational elements due to their absence. The concentrator perceives the wind flow from any side and creates a vortex motion inside itself due to curved channels. The outlet openings of the curved channels are directed to the blades of the wind wheel, which increases the maximum transfer of wind flow energy to the blades of the wind wheel. The vortex motion inside the concentrator creates a steady rotation of the wind wheel. An additional important point is the removal of the exhaust air flow from the vortex wind device. Existing wind farms have wind guidance mechanisms, which complicates the design, a stable rotation mode of the wind wheel is not created. All these problems of operating stations can be solved with the help of a vortex wind device